New Neurons in the Adult Mammalian Brain: Synaptogenesis and Functional Integration - Song, Hongjun (2005)
New neurons are continuously added in the olfactory bulb and dentate gyrus of the hippocampus throughout adult life (Kem- permann and Gage, 1999; Temple and Alvarez-Buylla, 1999; Schinder and Gage, 2004; Lledo and Saghatelyan, 2005; Ming and Song, 2005). This adult form of neurogenesis represents a previ- ously unrecognized structural and functional plasticity in the ma- ture mammalian brain, including in humans. Now it is well es- tablished that adult-born dentate granule cells (DGCs) can functionally integrate into the existing circuitry (Carlen et al., 2002; van Praag et al., 2002; Jessberger and Kempermann, 2003; Schmidt-Hieber et al., 2004). However, little is known about how that occurs and what is the contribution of new DGCs to the overall hippocampal function. Accumulating evidence suggests that adult neurogenesis is involved in many physiological and pathological conditions, such as learning and memory, epilepsy, mental disorders, and degenerative neurological diseases (Ming and Song, 2005). The impact of new neurons on the adult neu- ronal circuitry is determined by their physiological properties and synaptic connectivity. This mini-symposium presented at the 2005 Society for Neuroscience Meeting will provide insight into how newly generated neurons become synaptically inte- grated into the existing circuitry of the adult brain, with emphasis on the physiological properties of newborn DGCs in the hippocampus.